Guidelines for iron supplementation for Prophylaxis of Anemia in a National Programme - A Review - Mondal, Ankita; Thomas, Tinku; Swaminathan, Sumathi; Rao, Sanjukta; Varghese, Jithin Sam; Kulkarni, Bharati; Sachdev, Harsh Pal Singh; Kapil, Umesh; Kurpad, Anura V (Indian Journal of Community Health, 2018)
Recent National Family Health Survey-4 data shows that anaemia continues to be a major public health problem in India. In India much of the anaemia is due to iron deficiency, and women and children are at the greatest risk of anaemia. TheMinistry of Health and Family Welfare took a policy decision, in 2013, to develop the National Iron+ Initiative (NIPI) to address the prevailing iron deficiency anaemia. This initiative covered pregnant and lactating women, children and adolescents. However, the guidelines do not match the current World Health Organization (WHO) guidelines for prevention of iron deficiency anaemia in these population groups. The background evidence for the WHO and NIPI is thus reviewed to come to a common consensus on the optimum recommendation of iron supplementation for the population, while taking into consideration the feasibility of the program, without burdening the groups with iron over-dose. However, from the present review, there is a need for increased number of trials in India that could qualify for a high grade of evidence to support the guidelines of NIPI.